2012
DOI: 10.1007/s00122-012-1951-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTL for Fusarium head blight resistance and morphological and developmental traits in three backcross populations derived from Triticum dicoccum × Triticum durum

Abstract: Breeding for resistance to Fusarium head blight (FHB) in durum wheat continues to be hindered by the lack of effective resistance sources. Only limited information is available on resistance QTL for FHB in tetraploid wheat. In this study, resistance to FHB of a Triticum dicoccum line in the background of three Austrian T. durum cultivars was genetically characterized. Three populations of BC1F4-derived RILs were developed from crosses between the resistant donor line T. dicoccum-161 and the Austrian T. durum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 73 publications
9
106
0
Order By: Relevance
“…Positions of the QTL on 3B and 6B overlapped with those of the well documented genes Fhb1 and Fhb2 , respectively, which were fi rst described in the hexaploid cultivar Sumai-3 (Buerstmayr et al 2009 ). Allele survey at these loci by Buerstmayr et al ( 2012 ) revealed different SSR marker haplotypes between tetraploid lines and Sumai-3. The existence of resistance improving alleles at these loci in tetraploid wheat may circumvent the need to transfer resistance from hexaploid Asian sources into durum wheat.…”
Section: Sfimentioning
confidence: 66%
See 2 more Smart Citations
“…Positions of the QTL on 3B and 6B overlapped with those of the well documented genes Fhb1 and Fhb2 , respectively, which were fi rst described in the hexaploid cultivar Sumai-3 (Buerstmayr et al 2009 ). Allele survey at these loci by Buerstmayr et al ( 2012 ) revealed different SSR marker haplotypes between tetraploid lines and Sumai-3. The existence of resistance improving alleles at these loci in tetraploid wheat may circumvent the need to transfer resistance from hexaploid Asian sources into durum wheat.…”
Section: Sfimentioning
confidence: 66%
“…Durum wheat itself contributed resistance-improving alleles for the QTL on 2B (Gladysz et al 2007 ;Somers et al 2006 ), 3B (Buerstmayr et al 2012 ;Ghavami et al 2011 ) and 5B (Ghavami et al 2011 ). This backs up the idea that in current durum wheat a certain level of FHB resistance is already available.…”
Section: Qtl Studies In Tetraploid Wheatmentioning
confidence: 87%
See 1 more Smart Citation
“…Tetraploid relatives have proved to be an important source of FHB resistance (Prat et al 2014). QTLs conferring resistance were identified in T. carthlicum (Somers et al 2006), T. dicoccum (Buerstmayr et al 2012;Ruan et al 2012;Zhang et al 2014) and T. dicoccoides (Otto et al 2002;Chen et al 2007;Kumar et al 2007;Buerstmayr et al 2013), in some cases were mapped in similar positions as resistance QTLs described for hexaploid wheat.…”
Section: Cereal Research Communications 45 2017mentioning
confidence: 91%
“…Several studies have been so far successfully carried out to identify traits involved in FHB resistance in soft wheat (Triticum aestivum L.); whereas the sources of FHB resistance in durum wheat (Triticum durum Desf.) have not been fully identified yet (Buerstmayr et al, 2009(Buerstmayr et al, , 2012Jauhar and Peterson, 2009;Lionetti et al, 2015;Ruan et al, 2012). Durum wheat is by far more FHB-susceptible than soft wheat, and its susceptibility to FHB disease and mycotoxin accumulation in kernels is of particular concern in Italy because of its key role in pasta production (Bottalico and Perrone, 2002; This work aims at examining the behaviour of several durum wheat cultivars grown in a multi-year period in Italy in relation to deoxynivalenol content detected in kernels.…”
Section: Introductionmentioning
confidence: 99%